THE ROLE OF DISCUSSION IN GROUP COMMUNICATION AT BRIEFINGS TO MOTIVATE EMPLOYEES AT PT. WAHANA RAHARJA - Putri, Anisa Tranada (Universitas Sang Bumi Ruwa Jurai, 2024)
Study This discuss about the Role of discussion in communication group at the briefing For motivating employee at PT. Wahana Raharja ( Perseroda ) with use studies descriptive qualitative , Briefing is something briefing or the process of discussing existing ones in front of , something that is not yet happen . Briefings must given every moment to employees and subordinates For socialize existing rules and policies made with a purpose For discuss or track communication from on to lower become means superior For build connection with employee . Approach formally and non- formally through media briefings become sufficient alternative Good . So from That role the discussion during the briefing was very impactful positive for akryawan That artdi . Efforts with held briefing will make employee Keep going motivated For Spirit Work with through communication between superior with subordinate nor on the contrary or with fellow employee . If not often held briefing communication between employees and leaders or fellow employee That Alone will miscommunication occurred so that work No resolved with good and the targets that have been planned No according to what is expected .